Caso de estudio: Bitcoin como activo refugio para los mercados de valores de Perú y Chile durante el inicio de la pandemia del COVID-19 - Mantilla Mantilla, Juan Pablo Alfredo (2022)
Usually, when safe-haven assets are mentioned, the most common option that comes to mind is gold. Throughout history, this asset has offered investment alternatives in times of financial turbulence and high volatility. However, the increasing popularity of cryptocurrencies and their alternative to traditional cash, especially during the beginning of the COVID-19 pandemic, is undeniable. This study examines during the observation period from July 1, 2019 to April 6, 2020 (including within this period the declaration of the WHO COVID-19 pandemic) the relationship between the returns of the ETFs that represent the Peruvian and Chilean stock markets and the cryptocurrency (Bitcoin) to show whether the latter has provided diversification or safe haven benefits during turbulent times. According to the results obtained, we find that the most used cryptocurrency worldwide is not suitable to be considered as a safe haven in the short term. The results of the two GARCH models estimated for each stock market show that the daily returns of both countries tend to correlate positively with the Bitcoin cryptocurrency during the pandemic. The results of the regression also support the characteristics of Bitcoin as a useful asset for diversification of a possible stock portfolio of both countries. In the case of Chile, the cryptocurrency works as a better diversifier as it is less positively correlated than in the case of its relationship with the returns of the ETF representing the Peruvian stock market. A final portfolio analysis shows that through the CVaR methodology, including this cryptocurrency in two portfolios, one containing the iShares MSCI Peru ETF and the other with the iShares MSCI Chile ETF, has an insignificant impact on returns, risk and expected loss of the portfolio for the period under study.